2015
DOI: 10.1039/c5cs00486a
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocifen type anti cancer drugs

Abstract: Despite current developments in therapeutics focusing on biotechnologically-oriented species, the unflagging utility of small molecules or peptides in medicine is still producing strong results. In 2014 for example, of the 41 new medicines authorized for sale, 33 belonged to the category of small molecules, while in 2013 they represented 24 of 27, according to the FDA. This can be explained as the result of recent forays into new or long-neglected areas of chemistry. Medicinal organometallic chemistry can prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
398
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(411 citation statements)
references
References 75 publications
8
398
1
4
Order By: Relevance
“…[18,19] The most interesting results have been obtained with ferrocene derivatives, and in particular with the ferrocifen-type complexes. [17,[20][21][22][23][24][25] We recently prepared an iron(II) cyclometalated compound, [Fe(CO) 2 (phpy) 2 ] (phpyH = 2-phenylpyridine), and found that its activity on HTC116 and AGS cell lines was relatively moderate (IC 50 in the 25 μM range), presumably as a result of its instability in solution. [26] To stabilize the complex, while maintaining the advantages of the carbonmetal σ-bond, we considered that the use of pincer ligands would be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] The most interesting results have been obtained with ferrocene derivatives, and in particular with the ferrocifen-type complexes. [17,[20][21][22][23][24][25] We recently prepared an iron(II) cyclometalated compound, [Fe(CO) 2 (phpy) 2 ] (phpyH = 2-phenylpyridine), and found that its activity on HTC116 and AGS cell lines was relatively moderate (IC 50 in the 25 μM range), presumably as a result of its instability in solution. [26] To stabilize the complex, while maintaining the advantages of the carbonmetal σ-bond, we considered that the use of pincer ligands would be of interest.…”
Section: Introductionmentioning
confidence: 99%
“…These functionalized ferrocene derivatives and their metal complexes represent an important topic of research in many fields such as organic synthesis, catalysis, asymmetric catalysis, materials chemistry, and in medicine as antimalarial or antitumor agents. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In particular, ferrocenyl phosphines have been studied thoroughly, as represented by the well-known 1,1′-bis(diphenylphosphino)ferrocene (dppf ). [1] Some of us have described the formation of several amidephosphines containing ferrocene units, studied their coordination chemistry, [17,18] and also showed that some gold and silver complexes are active as antitumor agents.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep uterine cytosol prepared in buffer A (0.05 M Tris-HCL, 0.25 M sucrose, 0.1 % -mercaptoethanol, pH 7.4 at 25°C) as described previously [3] was used as a source of ERα. Aliquots (200 mL) of ERα in glass tubes were incubated for 3 h at 0°C with [6, H]-E 2 (2 × 10 -9 M, specific activity 1.62 TBq/mmol, NEN Life Science, Boston, MA) in the presence of nine concentrations of the ferrocenyl complexes to be tested (between 6 × 10 -7 and 6 × 10 -9 M for the complexes with RBA values higher than 5 % and between 6 × 10 -6 and 6 × 10 -8 M for the compounds with RBA values lower than 5 %) or of 17 -E 2 (between 8 × 10 -8 and 7.5 × 10 -10 M). At the end of the incubation period, the fractions of [ 3 H]-E 2 bound to the estrogen receptors (Y values) were precipitated by addition of 200 mL of a cold solution of protamine sulfate (1 mg/ mL in water).…”
Section: Biological Methodsmentioning
confidence: 99%
“…[3][4][5][6][7] In hormone-dependent cells, this effect is essentially mediated by interaction with the estradiol receptor and reversed by the addition of estradiol. In contrast, the antiproliferative effect observed in hormone-independent cells such as MDA-MB-231 cells is a cytotoxic effect.…”
Section: Introductionmentioning
confidence: 99%